Pulse Oximetry is Essential in Home Management of Elderly COVID-19 Patients (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Coronavirus disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2) is in Pandemic form and has affected people of 215 countries. It produces symptoms like fever, cough, shortness of breath, sore throat, headache, loss of taste, smell or appetite and many other rare symptoms. But the most important symptom is shortness of breath due to hypoxia. In a normal individual oxygen saturation (SpO2) is at least 95% and patient feels shortness of breath when SpO2 falls below 90% with some exception. SARS-CoV-2, a newly emergent coronavirus has the peculiarity to produce silent hypoxia, meaning SpO2< 90% or less like 80%, 70%, 60% without shortness of breath. Silent hypoxia can be diagnosed by monitoring SpO2 with pulse oximeter. For management of COVID-19, early symptoms like fever & cough, SpO2 should be monitored by pulse oximeter, followed by immediate correction of hypoxia by O2 supplementation and prophylactic oral or injectable anticoagulant to prevent thromboembolism and thus death rate can be reduced.Case summary: A 72-year-old man presented with the complaints of fever and headache followed by cough, fatigue, anorexia, loss of taste and appetite in next few days but no shortness of breath. The patient was clinically diagnosed as a case of COVID-19 & positive result of Real time-Polymerase Chain Reaction (RT-PCR) test confirmed the diagnosis. From the first day, SpO2 was regularly monitored with pulse oximeter and SpO2 on day 1, it was 96-98%. On day 8, SpO2 fell to 89-93%, pulse 96/min, respiratory rate>30/min, temperature 101° F, taste sensation was reduced. According to sign and symptoms, the patient was diagnosed as COVID-19 with severe pneumonia. Management was started at home with continuous monitoring, lying in prone position for 5-6 hours/day, supplemental oxygenation to maintain level of SpO2 between 94-96%, injectable anticoagulant enoxaparin to prevent venous thromboembolism (VTE) and disseminated intravascular coagulation (DIC) was given. Prophylactic antibiotics and symptomatic treatment were also given.Results: According to this case report, patient’s SpO2 was monitored by pulse oximeter on first day; on day 08, SpO2 fell to 89-93% & on day 10, further dropped to 85-88% which indicated severe pneumonia but there was no complaint of breathlessness as it was silent hypoxia. Sometimes the patient spent 30 minutes or more in toilet and SpO2 used to fall to 82-83% without any subjective shortness of breath but with only mild heaviness of chest and cough. Therefore SpO2 monitoring by pulse oximeter is essential in early diagnosis of silent hypoxia. Correction of hypoxia by supplemental oxygenation and prevention of VTE and DIC by using anticoagulant was the mainstay of treatment and patient had significant improvement on day 14. The patient was managed completely at home except X-ray being done in a hospital.Conclusion: Fall of SpO2 in COVID-19 i.e. hypoxia (usually present as shortness of breath) or silent hypoxia can be diagnosed early by pulse oximeter or smart phone pulse oximetry apps. Early management by isolation, supplemental oxygenation and oral/injectable anticoagulation can prevent further events like Acute Respiratory Distress Syndrome (ARDS), respiratory failure followed by multiple organ failure (that may cause death). The authors advocate further clinical trial and research.Bangladesh J Otorhinolaryngol; April 2020; 26(1): 55-67